2018
DOI: 10.1080/15295192.2017.1337461
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ and Fathers’ Autonomy-Supportive and Controlling Behaviors: An Analysis of Interparental Contributions

Abstract: Objective. The goal of this study was to examine how mothers and fathers contribute to each other's autonomy supportive and controlling behaviors toward their child. Design. The participants were heterosexual parental dyads from two prospective studies (Study 1, n = 289; Study 2, n = 202). Mothers and fathers completed questionnaires assessing their autonomy supportive and controlling behaviors toward their adolescent child. Results. In both studies, results from structural equation modeling revealed reciproca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…The parental autonomy-supportive interpersonal style not only has beneficial effects on children, but also on the person who provides the autonomy support (Mabbe, Soenens, Vansteenkiste, van der Kaap-Deeder, & Mouratidis, 2018) and on the other parent, predicting a positive affective atmosphere at home and promoting the wellbeing and vitality of the other parent (Guay, Ratelle, Duchesne, & Dubois, 2018).…”
Section: Palabras Clave: Relaciones Paterno-filiales Estilo Parental mentioning
confidence: 99%
“…The parental autonomy-supportive interpersonal style not only has beneficial effects on children, but also on the person who provides the autonomy support (Mabbe, Soenens, Vansteenkiste, van der Kaap-Deeder, & Mouratidis, 2018) and on the other parent, predicting a positive affective atmosphere at home and promoting the wellbeing and vitality of the other parent (Guay, Ratelle, Duchesne, & Dubois, 2018).…”
Section: Palabras Clave: Relaciones Paterno-filiales Estilo Parental mentioning
confidence: 99%
“…In terms of their children's education, Filipino couples make mutual decisions given that their children's academic achievements are their source of pride and compensation for their sacrifices (Alampay, 2014). Therefore, it can be argued that the similarity in the perceived Filipino parents' childrearing behaviors could result from their partners' mutual influence which may be more salient in a period during which their children are confronted by developmental challenges (e.g., high school to college transition; Guay et al, 2018). Previous studies provide support for this argument.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting young children's autonomy helps them develop executive functions, emotional regulation, and prosocial behaviors (Dix et al, 2007;Matte-Gagné et al, 2015). Parents' support of their children's independence is also associated with children's adaptive behavior and higher academic achievement (Guay et al, 2018). For example, Majdandžić et al (2018) found that fathers' physical and verbal encouragement of the child) has a protective role against anxiety development in preschoolers.…”
Section: The Parenting Pentagon Model (Ppm)mentioning
confidence: 99%